(untitled) (Perioperaciina Medicina, 2020)
With increasing maternal age caesarean section rates increase every year. Neuraxial anaesthesia is a method of choice for caesarean section; wide implementation of it has resulted in the reduction of maternal mortality from anaesthesia complications. Neuraxial anaesthesia also lets the patient remain conscious during birth as well as actively participate in the delivery. On the other hand, levels of stress and anxiety are higher compared to vaginal birth, consequently, in a few cases, sedation is needed. There is described a lot of sedation methods including using nitrous oxide, propofol, benzodiazepines, opioids, and dexmedetomidine. Considering the results of studies published in contemporary literature, safe sedation can be provided, even prior to the beginning of cesarean section and anaesthesia.